Medic! : how I fought World War II with morphine, sulfa, and iodine swabs - Franklin, Robert J. (Robert Joseph), 1917- (University of Nebraska Press, 2006)
Lt. Gen. George S. Patton remarked that the "45th Infantry Division is one of the best, if not the best division that the American army has ever produced." Such praise came at a steep price, for the 45th saw some of the fiercest fighting in the European campaign-from Sicily to Anzio and from southern France into Germany-and racked up one of the highest casualty rates. Through it all, medic Robert "Doc Joe" Franklin-drafted in 1942 and thrust into combat with no specific training or knowledge for treating war wounds-soldiered on, fighting as hard to keep his men alive as the enemy fought to kill them. His medical story, one of the first of World War II, is told here with simplicity, unflinching honesty, and grit. Studded with memorable vignettes, Franklin's memoir documents the almost unbearable drama of ground gained and lives lost as well as the terrible human toll of battle on himself, his comrades, and civilians quite literally caught in the crossfire. A rare look at the fight for lives laid on the line, Medic! brings to life as never before the reality of war